REFORMA AGRARIA BELUM BERAKHIR - Jaka Ferdian, Komang; Ode, Samsul (JUSS (Jurnal Sosial Soedirman), 2018)
Deforestation is currently a new challenge for Indonesia as a result of massive state enterprises or private actions that land conversion. Indonesian land conversion have an impact on environmental degradation are detrimental to society both in the surrounding woods. Policy at the governments Agrarian Reform Joko Widodo and Jusuf Kalla to be a solution to reduce land conversion action. This article wants to learn about the agrarian reform policy which has been running 3 years Administration Joko Widodo as well as models of indigenous community-based land redistribution. The method used in this article is a qualitative descriptive approach that describes the results of research, assessment and other references reinforced with empirical data based on literature, documents, and media.This article explains a few things, first, based forest management implemented for the public to support the welfare and maintaining the forest environment. Indigenous peoples in managing and protecting the forests have rules that have been derived from the ancestors. Forest management by indigenous peoples based on the belief give good impact to protect the environment. Second, the government agrarian reform policy Joko Widodo and Jusuf Kalla in the third year are still encountering a variety of problems that occur are confusion regulation occurs at the level of the central government, where the government issued Presidential Decree 88 in 2017 which is counterproductive to conflict resolution through agrarian reform. Object Land Agrarian Reform is not based on the needs of society but to refer the forest cover in accordance with the Regulations of Forestry, it makes Java, Lampung, and Bali sealed from agrarian reform policies. Agrarian Reform institutions to manage unclear because until now there is no institutional ad-hoc. Implementation of agrarian reform policies led directly by the president and multiple government agencies.